Analisis Komparatif Partisipasi Masyarakat dalam Pengelolaan Sampah: Studi Kasus Kawasan Perkotaan Polewali dan Pesisir Binuang, Kabupaten Polewali Mandar - Suardi, Putri Arianti; Mahful, Rafid; Suriadi, Nur Adyla; Chairunnisa, Chairunnisa (Jurnal Noken: Ilmu-Ilmu Sosial, 2025)
The differences in the characteristics of urban and coastal areas create unique waste management challenges, particularly related to suboptimal levels of community participation. This study comparatively examines the level of community participation in waste management between the Polewali Urban Area and the Binuang Coastal Area, Polewali Mandar Regency, West Sulawesi. Another objective is to identify barriers and community expectations in both locations. This study used a mixed-methods approach, combining quantitative data through a survey of 806 respondents and qualitative data through in-depth interviews with stakeholders. The study results show significant differences in participation. The Polewali Urban Area has a relatively balanced level of participation between those who have and have not participated. In contrast, participation in the Binuang Coastal Area is still identified as very low. It was found that the barriers in Binuang are fundamental, such as a lack of facilities and low awareness, while in Polewali the barriers are more operational, namely limited time and uneven distribution of facilities. These findings emphasize the need for different policy interventions, tailored specifically to the social characteristics and infrastructure availability in each region, rather than a single strategy.